Peran Kewirausahaan Syariah dalam Meningkatkan Ekonomi di Era Digital - Dewi Khayyirah; Nanda Puspitasari; Chairunisa Indri Rahmatika; Herlina Yustati; Andi Andi (Jurnal Manajemen Bisnis Era Digital, 2025)
In order to improve the development of Islamic businesses, business actors are advised to improve their understanding of sharia principles, develop innovative products that meet market needs, and implement ethical marketing strategies. The government needs to take supportive policies, such as issuing regulations that facilitate the development of Islamic businesses, providing education and training programs for business actors, and facilitating access to financing through financial institutions that offer Islamic products. For future research, it is recommended to conduct case studies on successful sharia business actors, analyze the impact of government policies on the growth of this industry, and conduct comparisons with other countries that have more advanced sharia industries to gain insights and best practices that can be applied.